The Beginning of Idolatry in Arabian Peninsula: An Analytical Study - Mian Swaiz Nadeem; Dr. Hafiz Tahir Islam; Muhammad Riffat Khan (`, 2025)
Arabian Peninsula has a rich history, not only famous for Islam but also it has a deep history for Abrahamic Religions. One of the sons of Abraham was known as Ismael. He led his tribe in Makkah and around the several areas of Arab. People were performing Hajj and the other religious obligations perfectly. After some times, the people of Arab forgot the teachings of Abraham and his son Ismael. Idol worship was introduced and promoted by Amr Bin Luhai,a profound leader of Arab. He took some of the idols from Syria and came back to Makkah and called the people to worship these idols. After this, Medina, Taif and several more places adopted idolatry. Every tribe created his own personal Idol to worship. This idol worship is identical to the Hinduism. Both the Cultures adopted the idol worship, but both of them are agreed that they don’t worship idols but instead they believe the idols a source of pray to God. This article discuses about the beginning of Idolatry in Araba before the Prophet Muhammad (SAW). Keywords: Idol worship, Makkah, Arab, Abraham.